2021
DOI: 10.1590/1809-4392201904462
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity of methanolic extracts from cutaneous secretions of Amazonian amphibians against phytopathogens of agricultural interest

Abstract: The biochemical defense mechanisms of amphibians involve cutaneous secretions of bioactive molecules with antimicrobial activity. This study evaluated the in vitro activity of methanolic extracts from cutaneous secretions of two amphibian species of the Bufonidae family, Rhaebo guttatus and Rhinella marina, in the control of the phytopathogens Fusarium udum, Fusarium solani, Colletotrichum truncatum, Aspergillus flavus, Rhizoctonia solani, Macrophomina phaseolina, and Calonectria pseudometrosideri. The R. gutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In Brazil, the most extensively studied amphibian-derived skin secretions are from Rhinella marina (R. marina; Cururu toad), which contains compounds, such as marinobufagin, telecinobufagin, bufalin, marinobufotoxin, cholesterol, dehydrobufotenine, and suberoyl arginine (2,22,23). A variety of biological effects have been attributed to the compounds in R. marina skin secretions extracts, including cytotoxic, immunomodulatory, antifungal, antimutagenic, and anti-plasmodial activities (9)(10)(11)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, the most extensively studied amphibian-derived skin secretions are from Rhinella marina (R. marina; Cururu toad), which contains compounds, such as marinobufagin, telecinobufagin, bufalin, marinobufotoxin, cholesterol, dehydrobufotenine, and suberoyl arginine (2,22,23). A variety of biological effects have been attributed to the compounds in R. marina skin secretions extracts, including cytotoxic, immunomodulatory, antifungal, antimutagenic, and anti-plasmodial activities (9)(10)(11)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to R. marina, another common frog species in Brazil is R. guttatus, particularly in the Amazon Basin; however the compounds in their skin secretions are poorly characterized (2,5). Some compounds were identified, such as N-methyl-5-hidroxytryptamine, bufotenine, dehydrobufotenine, 3β,16 β-dihydroxybufa-8 (14),20,22-trienolide, marinobufagin, and bufatrienolides (2,7,8), and biological effects have been reported in the literature, including cytotoxic, anti-plasmodial, fungicidal, hemolytic and antimutagenic activities (8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies that have demonstrated the biological activity as the effects that extracts from the secretion of the parotoid gland of R. guttatus exhibit hemolytic and cytotoxic activity against tumor and non-tumor cells (Ferreira et al 2013); toxic activity against Plasmodium falciparum and phytopathogenic fungi (Banfi et al 2016;Raasch-Fernandes et al 2021); mutagenic and antimutagenic (Oliveira et al 2019); nociception properties (Mailho-Fontana et al 2014) and immunomodulatory activity (Pelissari et al 2023).…”
Section: Introductionmentioning
confidence: 99%